Losses in the regenerator and the critical sections of a travelling wave thermoacoustic engine - Khoo, David Wee Yang (2016)
Thermoacoustic engine (TAE) can be used to convert heat from any source into electrical energy. Despite the theoretical efficiency of the cycle is very close to the Carnot cycle efficiency but due to many practical reasons, the actual efficiency of the engine is still very low. In order to enhance the overall efficiency of the waste-heat driven thermoacoustic engine (WHTAE), it is important to understand and identify the sources of losses in the engine components as well as to suggest design modifications on some critical components in the engine. All the studies reported to date are mainly focusing on the optimisation of the regenerator and the resonator without taking into consideration some of the important issues. One common trait of all the previous optimisation efforts is that the acoustic energy dissipation through the regenerator and the loop (or bends) were not well explained. It should be noted that this study provides a more comprehensive discussion on the acoustic field and the loss mechanisms between the regenerator and the sharp bend (torus-like section) in association with the radiant heat exchanger (RHX) of a WHTAE. In this work, a simplified solution and a numerical investigation are implemented to study the convection and radiation heat transfer between the regenerator and the RHX in two of the SCORE engine configurations. Both simplified solution and numerical results reveal that bulge is about three times better in total radiation heat transfer compared to the convolution. Based on the numerical results obtained, the design of the bulge show about five times more in total radiation versus convection to the regenerator top surface. The multi microphone least square technique is employed in conjunction with impedance tube measurement method to determine the acoustic properties of the tested specimen in order to develop an experimental modelling of a TAE that works in travelling-wave condition by using absorbing materials. Eight materials and combinations are investigated to realise that using an elastic end works best for low frequency attenuation applications. The selection of the attenuation material or combination of materials should be done very carefully and is strongly dependent on the target frequency. No material can work better for all frequencies. Some of the materials are suitable for high frequency but not suitable for low frequency attenuation applications. The acoustic energy losses through the regenerator and the RHX are determined by utilising the multi-microphone travelling-wave technique. It was found that when more than 30 layers of regenerator, more flow resistance is generated, there is no significant increase in the regeneration effect. Therefore, it is unbeneficial to add more than 30 layers of mesh. Owing to the perfect contact between the working fluid (gas parcels) and the solid material, the dissipation in the regenerator is dominated by viscous losses in both ambient and hot conditions. When imposing a temperature gradient across the regenerator, the system encounters more amplification than attenuation. Straight tube has the least acoustic energy dissipation and the highest loss in acoustic energy is obtained by the convolution RHX configuration. The loss in acoustic energy for the straight tube is mainly due to the viscous losses in the regenerator while the acoustic dissipation for the RHX configuration is mainly caused by the vortices generated at the two 90 o sharp bends and the sudden change of cross-sectional area. A thermoacoustic software, DeltaEC is employed to predict the acoustic energy dissipation through the regenerator and the RHX. The numerical model is found to predict the experimental results of the acoustic energy losses accurately. The DeltaEC models can be used to help on the design of future prototypes and for better optimisation of the TAEs.